Trend Factor in China: The Role of Large Individual Trading - Liu, Yang; Zhou, Guofu; Zhu, Yingzi (The Review of Asset Pricing Studies, 2024)
Abstract We propose a novel trend factor for the Chinese stock market that incorporates both price and volume information to capture dominant individual trading, momentum, and liquidity. We find that volume plays a more significant role in the trend factor for China than for the United States, reflecting the greater retail participation in China. By incorporating this trend factor into the 3-factor model of Liu et al. (2019), we propose a 4-factor model that explains a wide range of stylized facts and 60 representative anomalies. Our study highlights the important role of individual trading in asset pricing, especially in China. (JEL G12, G14, G15)